2016
DOI: 10.1590/1807-2577.09515
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of friction produced by self-ligating, conventional and Barbosa Versatile brackets

Abstract: ResumoIntrodução: O bráquete Barbosa Versátil apresenta um desenho que pode promover menor resistência friccional e maior deslize. No entanto, nenhum estudo in vitro avaliou seu mecanismo de deslize e resistência ao atrito, mesmo quando comparado com outros bráquetes autoligados ou convencionais. Objetivo: Comparar a resistência ao atrito entre bráquetes autoligados (EasyClip/ Aditek, Damon MX/ Ormco e In Ovation R/ GAC), convencionais (Balance Roth/ GAC, and Roth Monobloco/ Morelli) e o bráquete Barbosa Versá… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 24 publications
2
5
1
Order By: Relevance
“…The lower friction values observed in the presence of passive self-ligating brackets would result from the smaller surface of contact between the archwire and internal part of the slot, resulting from the absence of pressure exerted by the clip of this bracket. The findings of this study corroborated those of previous studies in which it was proved that the increase in contact surface increased the friction 1,2,5,7,11,13,14,16,18,24 .…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The lower friction values observed in the presence of passive self-ligating brackets would result from the smaller surface of contact between the archwire and internal part of the slot, resulting from the absence of pressure exerted by the clip of this bracket. The findings of this study corroborated those of previous studies in which it was proved that the increase in contact surface increased the friction 1,2,5,7,11,13,14,16,18,24 .…”
Section: Discussionsupporting
confidence: 92%
“…Our findings corroborated the results found by researchers when they made a comparison between self-ligating and conventional brackets, in which the lower frictional resistance would only be observed when these brackets were combined with wires with smaller diameters. These results would be justified by the reduction in the surface of contact between the slot and archwire 1,2,5,11,13,14,24,26,29 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this research, the authors found that the self-ligating and conventional metal brackets produced similar frictional forces in the sliding technique, in disagreement with the others studies [22][23][24] who tested self-ligating and conventional metal brackets, and concluded that the frictional force values found were higher in the conventional brackets, one of the justifications for this result, according to the authors, would be that no elastic was used, thus making the wire run more easily through the self-ligating bracket, allowing a lower force and faster tooth sliding.…”
Section: Discussioncontrasting
confidence: 89%